BRANDING IMPACT IN HOSPITALS - Wuisan, Dewi; Bernarto, Innocentius; Bambang, Robertus Maria; Antonio, Ferdi; Aristo, Benny (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This study aims to explore the influence of hospital branding on patient perception, satisfaction, and loyalty. A strong hospital brand can enhance patient trust and satisfaction, which in turn increases patient loyalty. The material presented includes an introduction to the brand and its impact on the hospital. The participants included 104 individuals from all Siloam hospital group hospitals who hold managerial positions, including doctors and healthcare professionals. This result indicates the importance of effective brand management in the healthcare sector to achieve competitive advantage, with 90% of participants understanding this. These findings have practical implications for hospital managers in developing marketing strategies focused on brand building and strengthening.